PRINCIPLE, CONCEPTS, THEORIES AND MANAGEMENT OF CRIMINAL JUSTICE SYSTEM - Doljerm, Ingkarad (Rangsit Journal of Law and Society, 2022)
Besides the knowledge and the understanding of the laws regarding the criminal justice process, the management of the criminal justice system is also important, in order to create the effectiveness in the judicial practices, and to provide the justice to the people in the society, in accordance with the theories and the goals of the criminal justice procedure, as well as to protect the rights and the liberties of the people, and the democracy under the rule of law. Thailand’s lack of well-organized criminal justice administration has led to the problems and the obstacles in the finding of the facts in criminal cases, manifested in the continued errors, such as in the cases of Cherry Ann and Kru Jomsup etc. Therefore, the study recommends that there should be in-depth study of the principles and the theories concerning the judicial administration, and putting them into practices. By this approaches, the flaws in the practices shall be eliminated and the sustainable, effective and efficient justice administration shall be established, whether as the conducts of the administrators, police officers, prosecutors, the courts, the correctional workers, or the other organizations related to the judicial process, such as the department of forensic science, and the entities related to the protection of rights and liberties etc. which affects the administration, cutting off the process of childbearing fairly fair and impartial to save the people and society according the golds like a liberal democracy and under the rule of law.